2019
DOI: 10.1534/genetics.119.302165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insulators in Transgene Transvection in Drosophila

Abstract: Precise activity of a gene requires its promoter to be matched with an appropriate enhancer. Insulators are DNA elements which can limit inappropriate enhancer-promoter interactions. More recently, their ability to stimulate gene activity has been also recognized... Transvection is the phenomenon where a transcriptional enhancer activates a promoter located on the homologous chromosome. It has been amply documented in Drosophila where homologs are closely paired in most, if not all, somatic nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 113 publications
(147 reference statements)
3
9
0
2
Order By: Relevance
“…Our data clearly indicate that transvection can also be disrupted by the loss of small DNA elements, even when pairing is preserved. Consistent with our findings using endogenous alleles, insulators play roles in transvection between transgenes (Lim et al, 2018;Piwko et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Our data clearly indicate that transvection can also be disrupted by the loss of small DNA elements, even when pairing is preserved. Consistent with our findings using endogenous alleles, insulators play roles in transvection between transgenes (Lim et al, 2018;Piwko et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…studies independently found enrichment for DNA-binding architectural and insulator proteins in tight-pairing regions (AlHajRowley et al 2019), suggesting a potential role for these proteins in button function. In support of this view,Viets et al observed that genomic regions amenable to pairing are enriched in clusters of insulator proteins(Viets et al 2019), and previous works on the incorporation of insulator sequences into transgenes showed that these sequences can stabilize pairing and transvection(Lim et al 2018;Fujioka et al 2016;Piwko et al 2019). Notably, our analysis revealed a requirement for some degree of specificity between homologous buttons (Figure2-figure supplement 4A,B), since simulations of non-specific interactions between buttons did not result in robust pairing (Fig.…”
supporting
confidence: 82%
“…41 ), the observation that some insulator proteins and insulator elements promote transvection (refs. 16,19,42,43 , and reviewed by ref. 44 ), and the enrichment of architectural proteins at genomic sites involved in allelic interactions 27 .…”
Section: Resultsmentioning
confidence: 99%